STUDENTS' LEVEL OF SATISFACTION FOR THE PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2015)
Motivation constitutes itself in an element of vital importance in the teaching/learning process. Motivated student manifests himself/herself in his/her group through different behavior, such as: presents himself/herself active, respectful, participant, asks questions, cooperates with the classmates and teachers, shows happiness, interests for the his/her actions, repeats the exercises, in other words, feels pleasure and desire in taking motor activities and learning during the Physical Education classes. This study had the aim of investigating the satisfaction level for the Physical Education classes, of students who belong to State Public Schools from IV Secretaria de Desenvolvimento Regional  Chapecó/SC. Its sample was composed of 2048 students, aged 13 -16 years. To investigate the satisfaction level “IADOV” questionnaire modified by López (apud LÓPEZ & GONZÁLEZ, 2002) was used. For data analysis “IADOV” logic table modified by López (apud LÓPEZ & GONZÁLEZ, 2002) was used. The results presented for the Individual Satisfaction Level for the Physical Education classes demonstrate that: 51% from the students presented maximum level of satisfaction; 17% from the students demonstrate more satisfaction than dissatisfaction; 30% presented non-defined or contradictory satisfaction; 1% presented more dissatisfaction than satisfaction and 1% present themselves with maximum dissatisfaction. The Group Satisfaction Index of the sample presented the value of 0,58, which indicates satisfaction of these students in relation to the Physical Education classes. Through the results presented it can be concluded that, although the maximum satisfaction level being the most demonstrated in the students' options, the non-defined or contradictory level of satisfaction presented a high index, and must be reconsidered. This information serves as warning for the Physical Education professionals, and suggests that, the extrinsic and intrinsic motifs that influence the students' level of satisfaction must be observed.
Keywords: level of satisfaction; intrinsic motifs; extrinsic motifs.